Could Fertility-Sparing Surgery be Considered for Women With Early Stage Ovarian Clear Cell Carcinoma - Nasioudis, Dimitrios; Chapman-Davis, Eloise; Frey, Melissa K.; Witkin, Steven S.; Holcomb, Kevin (Journal of gynecologic oncology, 2017)
The aim of the present retrospective population-based study was to investigate the oncologic impact of uterine and ovarian preservation (OP) in premenopausal women with stage IA or IC ovarian clear cell carcinoma (OCCC). The National Cancer Institute's Surveillance, Epidemiology, and End Results (SEER) database was accessed and a cohort of surgically-staged premenopausal women (age <50 years) diagnosed with unilateral stage IA or IC OCCC was drawn. Based on site-specific surgery codes, women who did not undergo hysterectomy and/or bilateral salpingo-oophorectomy (BSO) were identified. Overall survival (OS) and cancer-specific survival (CSS) rates were calculated following generation of Kaplan-Meier curves; comparisons were made with the log-rank test. Multivariate Cox analysis was performed to control for possible confounders. A total of 741 premenopausal women who met the inclusion criteria were identified. Based on available information, rate of uterine preservation was 14.5% (96/663) while the rate of OP was 28.1% (71/253). Five-year CSS rates were 90.8% for women who did not undergo hysterectomy compared with 87.7% for those who did (p=0.290). Similarly, 5-year CSS rates in the OP and BSO groups were 92.6% and 85%, respectively (p=0.060). After controlling for disease sub-stage (IA vs. IC), uterine or OP was not associated with a worse overall or cancer-specific mortality. In the present cohort, uterine and OP did not have a negative impact on oncologic outcomes. Selection criteria for fertility-sparing surgery (FSS) could be expanded to include women with stage IA OCCC.